2016
DOI: 10.1111/asj.12740
|View full text |Cite
|
Sign up to set email alerts
|

Selection for high and low oxygen consumption‐induced differences in maintenance energy requirements of mice

Abstract: Maintenance energy requirements (MER) of mice selected for high (H) or low (L) oxygen consumption (OC) were compared. Forty-four mice from H and L OC lines were weaned at 3 weeks and divided into four experimental groups: group A were sacrificed at 4 weeks; group B were fed ad libitum, and groups C and D were fed 2.8 and 2.4 g/day, respectively, from 4 to 8 weeks of age. Groups B-D were sacrificed at 8 weeks. Chemical components were estimated for all groups. MER was estimated using a model that partitioned me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 14 publications
2
14
0
Order By: Relevance
“…Significant differences in FCR (Hong et al, ,) and MER (Darhan et al, ) between the H and L mouse lines were previously reported. In the present study, RFI was calculated from FI measurements in 37 mice of the 16th generation.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Significant differences in FCR (Hong et al, ,) and MER (Darhan et al, ) between the H and L mouse lines were previously reported. In the present study, RFI was calculated from FI measurements in 37 mice of the 16th generation.…”
Section: Discussionmentioning
confidence: 86%
“…It has been reported that the proton leak is associated with MER (rat: Rolfe & Brand, 1996;Rolfe & Brown, 1997;poultry: Luiting, Schrama, Hel, & Urff, 1991). We reported previously that a high-OC mouse line had significantly higher MER than a low-OC mouse line (Darhan et al, 2017). As the liver mitochondrial proton leak was higher in the H than in the L line, the basal metabolic rate clearly differed between them.…”
Section: Comparison Of Mitochondrial Respiratory Activitymentioning
confidence: 81%
See 1 more Smart Citation
“…Genetics Selection Evolution, 24, 487-509. https://doi.org/10.1186/1297-9686-24-6-487 Meyer, K., & Tier, B. (2012 (Darhan et al, 2017(Darhan et al, , 2019Hong et al, 2013Hong et al, , 2015. OCMBW: OC per metabolic body weight; AgH and AgL: high and low aggressive lines established by divergent selection by Kawamoto et al (1993).…”
Section: Discussionmentioning
confidence: 99%
“…Recent study showed that oxygen consumption was negatively associated with FE of mice. Also, the higher oxygen consumption mice have higher mitochondrial activity and energy expenditure than lower oxygen consumption mice [ 9 , 10 ]. These results indicated that energy metabolism was negatively related to FE in mice.…”
Section: Introductionmentioning
confidence: 99%